REVIEW: Runfola, A., Milanesi, M., and Guercini, S., Internationalization of Luxury Fashion Firms. Examining the Business Models of SMEs, Palgrave MacMillan, 2022. - Monteverde, Giulia (Piccola Impresa / Small Business, 2022)
Filling a gap in current literature, the book innovatively focuses the analysis on small- and medium-sized enterprises (SMEs) to investigate the internationalization of luxury fashion organizations and the relationship between internationalization and business models. Recognizing the key role of Italy in the luxury fashion industry, this book provides six in-depth case studies of Italian luxury fashion SMEs. The Authors then link the theoretical framework adopted with the results of their research to present the reasons and modes of internationalization of luxury fashion SMEs, and the implications for their business models.